Analysis of Competencies, Soft Skills, and Digital Literacy in the Era of Technological Disruption (Study on Undergraduate Accounting Study Program Students FEB University of Mataram) - Yuli Muliati; Eni Indriani (Cita Konsultindo Research Center, 2024)
The application and advancement of digital technology are two of the most prominent aspects of the 21st century. This development changes almost all aspects of human life, not only ways of communicating and entertainment but also the business world and company breakthroughs. This study aims to examine the effect of competence, soft skills, and digital literacy on the work readiness of accounting students. The population used in this study were 6th and 8th-semester students majoring in S1 Accounting at Mataram University. The sampling technique in this study was probability sampling with a purposive sampling type. The sample calculation in this study used the Slovin formula with an error rate of 5%. The final number of samples used in this study was 226. The data analysis conducted in this study is multiple linear regression analysis and will be tested using SmartPLS 3 with an inferential statistical model through structural equation modeling (SEM) analysis with partial least squares (SEM-PLS). These findings conclude that competence, soft skills, and digital literacy have a significant positive effect on work readiness. The results of these findings are expected to add insight and a treasure of knowledge, especially in terms of analyzing various factors of student work readiness. This research is expected to provide benefits for academics by enriching the literature regarding the analysis of competencies, soft skills, and digital literacy in the era of technological disruption.